Computational modeling of through-thickness flow and pressure drop characteristics in woven matrix porous media. (3rd May 2020) - Zhi, Z.; Chen, H.; Longtin, J. P.; Alkhader, M.; Venkatesh, T. A.
ABSTRACT: A hybrid finite element/volume model that captures the flow and pressure drop characteristics in highly porous woven matrix media is developed. It is demonstrated that the characteristics of flow through a woven matrix composed of fibers with circular cross-section can be modeled using the finite element method with an equivalent woven matrix system composed of fibers with square cross-section. From simulations of fluid flow in a range of models with varying sizes, it is demonstrated that changes in the thickness of the finite element model in the fluid flow direction and defects in the lay-up of the woven matrix layers have significant effects on the pressure drops. Higher defect densities result in greater pressure drops as they disrupt the steady flow of fluid in the through-thickness direction. The pressure drops obtained in the finite element model simulations of thick models that contained some defective layers match well with experimental observations.